Communication, semiotics, and the language Rubicon. Issue 1 (2nd January 2018) - Kozintsev, Alexander
ABSTRACT: Attempts at combining Uexküll's ideas with those of Peirce within a single quasi-discipline called 'biosemiotics' are ill-founded. Peirce's 'interpretant' sensu lato refers to two qualitatively different mental states, one relating to indexes and icons (INT 1) and the other to symbols (INT 2). Animal communication is dyadic – the referent is a directly induced mental state (INT 1). Glottocentric communication is triadic because the connection between symbol and INT 1 is mediated by INT 2. Whereas the gradualist view of glottogenesis is erroneous, Müller's and Chomsky's saltationist theories may imply that the idea of language Rubicon is anti-evolutionary. However, the views of Pavlov and Vygotsky and of their modern followers, Deacon and Tomasello, while being Darwinian, support the saltationist scenario. The emergence of the second signal system, of symbols, and of INT 2 was a psychological leap. In human communication, apart from the semiotic triangle (INT 1 – INT 2 – symbol), the dyadic relation between non-symbolic signs and INT 1 still holds. To Ekaterina Velmezova